Pedagogical strategies and teaching practices for the teaching of law (2003)
The author intends to recognize interdisciplinarity as a basis for the pedagogy of law, recognizing human rights, democracy. globalization and negotiation as new law forms. She insists on surpassing code and memory based pedagogies as the basis for the construction of an authentic academic community. She highlights the importance of constructing a student-teacher. relationship in social-legal knowledge.